Spatiotemporal changes in aerosols over Bangladesh using 18 years of MODIS and reanalysis data. (1st August 2022) - Ali, Md Arfan; Bilal, Muhammad; Wang, Yu; Qiu, Zhongfeng; Nichol, Janet E.; Mhawish, Alaa; de Leeuw, Gerrit; Zhang, Yuanzhi; Shahid, Shamsuddin; Almazroui, Mansour; Islam, M. Nazrul; Rahman, Muhammad Ashfaqur; et al.
Abstract: In this study, combined Dark Target and Deep Blue (DTB) aerosol optical depth at 550 nm (AOD550 nm ) data the Moderate Resolution Imaging Spectroradiometer (MODIS) flying on the Terra and Aqua satellites during the years 2003–2020 are used as a reference to assess the performance of the Copernicus Atmosphere Monitoring Services (CAMS) and the second version of Modern-Era Retrospective analysis for Research and Applications (MERRA-2) AOD over Bangladesh. The study also investigates long-term spatiotemporal variations and trends in AOD, and determines the relative contributions from different aerosol species (black carbon: BC, dust, organic carbon: OC, sea salt: SS, and sulfate) and anthropogenic emissions to the total AOD. As the evaluations suggest higher accuracy for CAMS than for MERRA-2, CAMS is used for further analysis of AOD over Bangladesh. The annual mean AOD from both CAMS and MODIS DTB is high (>0.60) over most parts of Bangladesh except for the eastern areas of Chattogram and Sylhet. Higher AOD is observed in spring and winter than in summer and autumn, which is mainly due to higher local anthropogenic emissions during the winter to spring season. Annual trends from 2003–2020 show a significant increase in AOD (by 0.006–0.014 year −1 ) over Bangladesh, and this increase in AOD was more evident in winter and spring than in summer and autumn. The increasing total AOD is caused by rising anthropogenic emissions and accompanied by changes in aerosol species (with increased OC, sulfate, and BC). Overall, this study improves understanding of aerosol pollution in Bangladesh and can be considered as a supportive document for Bangladesh to improve air quality by reducing anthropogenic emissions. Graphical abstract: Image 1 Highlights: Both satellite and reanalysis data show significantly higher AOD in Bangladesh. Higher AOD was found in spring and winter than in summer and autumn. Total AOD is significantly dominated by organic carbon, sulfate, and black carbon. Significant increasing trends in AOD were observed during 2003–2020. Increasing in anthropogenic emissions are responsible for AOD increasing trends.